Keutuhan Nada dan Makna dalam Susunan Bahasa Al-quran - Dedy Wahyudin; Djuaini A (El-Tsaqafah : Jurnal Jurusan PBA, 2019)
This article aimed to describe three focuses: first, how sounds oflanguage signify its meaning; second, how composition of sounds correspondsto the composition of meaning; and third, what are the proofs that the soundsof al-Qur’an verses compose its meanings. Research approach of this articleis qualitative approach using library research. Based on phonological andsemantic studies, this research concludes that the relation between wordsand its meaning in Arabic is natural relation; sounds of al-Qur’an thereforeindicates its meaning; and it can be proofed by analysing al-Qur’an fromphonological and semantic perspective